Prognostic Significance Of Fgfr3 And Egfr In Recurrent Muscle-Invasive Bladder Cancer - Tillashaykhov Mirzagaleb Nigmatovich; Boyko Elena Vladimirovna; Yusupov Sherali Khasanovich; Sulletbayev Nurjan Bakhtiyarovich; Dyu Alexander Vladimirovich (International Journal of Medical Sciences And Clinical Research, 2025)
The aim of this study was to evaluate the prognostic significance of FGFR3 and EGFR expression in recurrent muscle-invasive bladder cancer (MIBC). A total of 73 patients with histologically confirmed recurrent MIBC were included in the study. The expression levels of the markers were assessed using immunohistochemistry, and survival outcomes were evaluated using the Kaplan–Meier method and Cox proportional hazards model. High EGFR expression was associated with poor tumor differentiation, early recurrence, and a statistically significant decrease in 3-year overall survival (p = 0.003). FGFR3 showed moderate prognostic significance. In multivariate analysis, EGFR emerged as an independent risk factor (HR = 2.17; p = 0.006). The findings confirm the significance of EGFR as a prognostic biomarker in recurrent MIBC and highlight its potential as a target for personalized therapy.